جہاد کے منتخب احکامِ فقہیہ کی عصری اہمیت و معنویت:تفسیر احکام القرآن للجصاص کے تناظر میں: The Contemporary Significance and Relevance of Selected Jurisprudential Rulings on Jihad: In the Context of Aḥkām al-Qurʾān by al-Jaṣṣāṣ - Muhammad Ahmad; Dr. Fazail Asrar Ahmed; Dr. Muhammad Anas Raza (Al-Amīr Research Journal for Islamic Studies, 2025)
This research investigates the modern applicability of specific legal rulings (Fiqh) concerning Jihad, a central and often misunderstood principle in Islamic law. The study is necessitated by the urgent need to bridge classical jurisprudential scholarship with contemporary geopolitical realities and ethical dilemmas. Utilizing Imam Abu Bakr al-Jassas’s (d. 370 AH) influential exegesis, Tafsir Ahkam al-Qur’an, as its methodological framework, the paper interprets foundational Hanafi doctrines on Jihad to address present-day challenges. The analysis focuses on several core themes from Al-Jassas’s commentary, including the phased and primarily defensive prescription of armed struggle, which counters narratives of inherent aggression. It also examines the mandate for strategic readiness (isti’dad), the imperative of military discipline under legitimate command, and the humanitarian exemptions granted to non-combatants and the vulnerable. The paper argues that these classical principles correspond directly to modern concepts. For instance, strategic readiness finds parallels in contemporary military deterrence theory and intelligence gathering, while the insistence on state authority provides a legal basis for challenging the legitimacy of non-state militant actors. A significant finding is how Islamic law’s compassionate exemptions for the vulnerable foreshadow principles enshrined in modern international humanitarian law. In conclusion, this study posits that a historically informed and nuanced reading of Jihad through the work of Imam al-Jassas offers a sophisticated ethical-legal framework capable of addressing the intricate challenges of modern warfare, international law, and human rights. Keywords: Jihad, Hanafi Fiqh,Imam al-Jassas,Ahkam al-Qur’an,Islamic Military Ethics.